Safety, Tolerability, and Immunogenicity of a DNA Vaccine (pGX9501) Against SARS-CoV-2 in Healthy Volunteers: A Single-Center, Randomized, Double-Blind, Placebo-Controlled, and Dose-Ranging Phase I Trial - Haijing Yang; Yang Zhou; Xin Cheng; Chao Qiu; Shuo Wang; Yu Xia; Xuefen Huai; Zhenning Xiu; Jiarong Wang; Yue He; Guoying Cao; Qiong Wei; et al. (Vaccines, 2025)
Background: pGX9501 is a prophylactic DNA vaccine encoding the spike protein of SARS-CoV-2 and can induce immune response in the human body so as to prevent COVID-19. With respect to non-clinical studies, pGX9501 has been demonstrated to induce both cellular and humoral immune responses in various animal models. It was found that the level of antibody titers following a two-dose regimen was higher than that following a single-dose regimen in nonhuman primate challenge model. Methods: In China, a phase I, randomized, double-blind, placebo-controlled clinical trial has been conducted in Huashan Hospital, Shanghai, China to evaluate the safety, tolerability, and immunogenicity of DNA vaccine pGX9501 administered intradermally (ID) followed by electroporation (EP) in 45 Chinese healthy volunteers aged 18 to 59 years old. Results: No adverse events of special interest (AESIs), death, or treatment-related SAEs occurred in this study. All the treatment-related (vaccine or EP) adverse events (TRAEs) were of grade 1 and 2 in severity. The solicited AEs were reported in thirty-two (32/36, 88.9%) and nine (9/9, 100.0%) subjects, respectively, in the DNA vaccine and placebo group. The frequency of solicited AEs did not increase with vaccine dose level and frequency. The DNA vaccine pGX9501 effectively enhanced both humoral and cellular immune responses in a dose-dependent manner, with increased antibody GMTs and peak seroconversion rates observed on day 42. The significant rise in IFN-γ levels confirmed the vaccine’s ability to induce cellular immune responses. Variations in the microbiome structure suggested a tangible impact of the gut microbiota on vaccine immunogenicity. Conclusions: The findings from this study confirm the immunogenicity and safety of the DNA vaccine pGX9501 and point to the potential role of the gut microbiota in vaccine immune responses. These insights provide practical references for the future design and development of DNA vaccines.